Energetically favored formation of SnO2 nanocrystals as electron transfer layer in perovskite solar cells with high efficiency exceeding 19%. (October 2017) - Dong, Qingshun; Shi, Yantao; Zhang, Chunyang; Wu, Yukun; Wang, Liduo
Abstract: In fabrication of SnO2 electron transfer layer (ETL) via traditional solution routes, the strong dependence of film crystallization on high temperature annealing or robust thermal treatment makes it challengeable to prepare crystallized SnO2 ETLs at low temperature (< 150 °C). Here, we put forward a sol-gel route by which the whole fabrication process of crystallized SnO2 ETL below 80 °C is realized for the first time. In the new route, participation of atmosphere O2 and H2 O by refluxing is crucial as it can greatly promote Sn 2+ oxidation and controlled hydrolysis in SnCl2 ·2H2 O alcohol solution, in turn opening up an energetically favorable pathway for SnO2 crystallization at low temperature. Systematical investigations reveal that SnO2 ETLs have high conductivity and transmittance and appropriate energy band level, by which PSCs obtain superior photovoltaic performance, with a champion power conversion efficiency (PCE) and steady-state PCE of 19.20% and 18.48% achieved, respectively, much higher than that of the devices using high temperature annealed TiO2 ETLs (16.61% and 15.03%). The SnO2 -ETL-based flexible PSCs also attain a high PCE up to 16.11% and among the highest records of flexible PSCs. Due to a larger band gap, SnO2 -ETLs-based PSCs show superior UV resistance against high intensity UV light irradiation. Graphical abstract: Low temperature fabrication of SnO2 electron transfer layer (ETL) below 80 °C is realized by synthesis of SnO2 nanocrystals through an energetically favorable wet chemical route. The SnO2 -ETLs with high conductivity and transmittance, appropriate band edge and wide band gap endow planar PSCs with high efficiencies and superb UV resistance. Highlights: The whole fabrication process of crystallized SnO2 ETLs below 80 °C is realized using sol–gel route for the first time. Participation of atmosphere O2 and H2 O by refluxing is crucial for SnO2 crystallization in solution at low temperature. This SnO2 ETLs endow planar PSCs high PCEs of 19.20% and 16.11% on rigid and flexible substrates, respectively. Due to a large band gap (4.13 eV), SnO2 -ETLs-based PSCs show superior UV light stability.